Equine asthma syndrome: managing the environment. (2nd January 2022) - Neal, Chris
Abstract : Equine asthma syndrome is arguably the most common non-septic lower respiratory condition diagnosed in horses. In a hospital environment, it is important to be aware of its clinical signs, especially as many horses with the condition will go unnoticed by their owners. Prompt identification can help reduce morbidity within the hospital. Focus on environmental management practices, including feed, bedding and ventilation are well known to reduce the prevalence of the disease within the equine population. This review provides practical advice to equine professionals operating within a hospital environment to minimise respirable particle concentration and the incidence of equine asthma syndrome. A checklist is provided to allow interactive discussion with owners at discharge into how best to reduce the clinical signs of equine asthma syndrome at home.